equação do segundo grau -x²+2x-1.
Soluções para a tarefa
Respondido por
1
Olá!!!
Resolução!!!
- x² + 2x - 1 = 0 • ( - 1 )
x² - 2x + 1 = 0
a = 1, b = - 2, c = 1
∆ = b² - 4ac
∆ = ( - 2 )² - 4 • 1 • 1
∆ = 4 - 4
∆ = 0
x = - b/2a
x = - ( - 2 )/2 • 1
x = 2/2
x' = 1
x' = x" = 1
S = { 1 }
Espero ter ajudado!!
Resolução!!!
- x² + 2x - 1 = 0 • ( - 1 )
x² - 2x + 1 = 0
a = 1, b = - 2, c = 1
∆ = b² - 4ac
∆ = ( - 2 )² - 4 • 1 • 1
∆ = 4 - 4
∆ = 0
x = - b/2a
x = - ( - 2 )/2 • 1
x = 2/2
x' = 1
x' = x" = 1
S = { 1 }
Espero ter ajudado!!
Perguntas interessantes
Matemática,
11 meses atrás
Inglês,
11 meses atrás
Geografia,
11 meses atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Sociologia,
1 ano atrás
Matemática,
1 ano atrás